Field Tests on the Stress Characteristics of Enriched Water Tunnel Invert. (23rd January 2021) - Du, Mingqing; Li, Xiang; Wang, Xuchun; Teng, Hongwei; Zhang, Peng; Zhu, Zhen
Abstract : To monitor the changes in the force of the tunnel invert steel bars after the groundwater level changes, field tests were performed to accurately and comprehensively characterize the stress acting on the rebar of a tunnel invert. Changes in stress and temperature were monitored for two layers of rebar (upper and lower) in an actual tunnel invert during its repair. The results showed that the changes in stress followed different paths for the upper and lower layers. After the groundwater is replenished, the maximum tensile stress of the rebar was 17.3 MPa, and the maximum compressive stress was 120 MPa. Major changes in stress were observed 2–6 days after rain. Based on this, the seepage path of groundwater is analyzed. During this period, the compressive stress increased threefold, and the tensile stress increased 9.5-fold. The rebar stress in the tunnel invert followed a Gaussian distribution after stabilizing. Four phases of stress progression are identified and discussed. The results can provide data support and theoretical basis for the treatment of invert floor heave in enriched water tunnel.